Radiosurgery with flattening-filter-free techniques in the treatment of brain metastases: plan comparison and early clinical evaluationAusgleichsfilterfreie Radiochirurgie bei der Behandlung von Hirnmetastasen = Ausgleichsfilterfreie Radiochirurgie bei der Behandlung von Hirnmetastasen : ein Planvergleich und erste klinische Ergebnisse - Hörner-Rieber, Juliane; Tonndorf-Martini, Eric; Schramm, Oliver; Rhein, Bernhard; Kappes, Jutta; Hoffmann, Hans; Lindel, Katja; Debus, Jürgen; Rieken, Stefan (Strahlentherapie und Onkologie, 2016)
BackgroundRadiosurgical treatment of brain metastases is well established in daily clinical routine. Utilization of flattening-filter-free beams (FFF) may allow for more rapid delivery of treatment doses and improve clinical comfort. Hence, we compared plan quality and efficiency of radiosurgery in FFF mode to FF techniques.Materials and methodsBetween November 2014 and June 2015, 21 consecutive patients with 25 brain metastases were treated with stereotactic radiosurgery (SRS) in FFF mode. Brain metastases received dose-fractionation schedules of 1 × 20 Gy or 1 × 18 Gy, delivered to the conformally enclosing 80 % isodose. Three patients with critically localized or large (>3 cm) brain metastases were treated with 6 × 5 Gy. Plan quality and efficiency were evaluated by analyzing conformity, dose gradients, dose to healthy brain tissue, treatment delivery time, and number of monitor units. FFF plans were compared to those using the FF method, and early clinical outcome and toxicity were assessed.ResultsFFF mode resulted in significant reductions in beam-on time (p < 0.001) and mean brain dose (p = 0.001) relative to FF-mode comparison plans. Furthermore, significant improvements in dose gradients and sharper dose falloffs were found for SRS in FFF mode (−1.1 %, −29.6 %; p ≤ 0.003), but conformity was slightly superior in SRS in FF mode (−1.3 %; p = 0.001). With a median follow-up time of 5.1 months, 6‑month overall survival was 63.3 %. Local control was observed in 24 of 25 brain metastases (96 %).ConclusionSRS in FFF mode is time efficient and provides similar plan quality with the opportunity of slightly reduced dose exposure to healthy brain tissue when compared to SRS in FF mode. Clinical outcomes appear promising and show only modest treatment-related toxicity.